Pespiration rates and ethanol and ethylene production of mangoes stored under elevated carbon dioxide and reduced oxigen atmospheres - Bender, Renar João; Brecht, Jeffrey (Pesquisa Agropecuaria Brasileira, 2000)
The objective of this work was to evaluate respiration rates and ethanol and ethylene production of mangoes stored in controlled atmosphere (CA) with reduced O2 and elevated CO2 concentrations. Pre-climacteric 'Kent' and 'Tommy Atkins' mangoes were stored for 14 or 21 days at 12°C in 5%, 15%, 25%, 35%, 45%, 50% or 70% CO2 plus either 21%, 5% or 3% O2 in a flow through CA system at 12 °C. In the control treatment fruits were stored in air at the same temperature and also in the flow through system. After the CA storage the mangoes were transferred and kept for 5 days in air at 20 oC. Mangoes stored in either 50% or 70% CO2 had the highest ethanol production rates. The reduction to 3% of the O2 concentration in the storage atmosphere does not seem to have an additional effect on ethanol production. Respiratory rates of mangoes in CA above 45% CO2 atmospheres were higher than in the other treatments, while ethylene production rates were the lowest values. After transfer to air at 20 oC, respiration rates of mangoes from these treatments dropped significantly below control levels, which, associated with lower rates of ethylene production, indicate that the mangoes had been damaged by the elevated CO2 atmospheres.